Effect of VAChT reduction on lung alterations induced by exposure to iron particles in an asthma model - Tabata Maruyama dos Santos; Renato Fraga Righetti; Leandro do Nascimento Camargo; Edna Aparecida Leick; Silvia Fukuzaki; Elaine Cristina de Campos; Thiago Tafarel Galli; Beatriz Mangueira Saraiva-Romanholo; Luana Laura Sales da Silva; Jéssica Anastácia Silva Barbosa; Juliana Morelli Lopes Gonçalves João; Carla Máximo Prado; et al. (BMC, 2024)
Abstract Introduction Pollution harms the health of people with asthma. The effect of the anti-inflammatory cholinergic pathway in chronic allergic inflammation associated to pollution is poorly understood. Methods One hundred eight animals were divided into 18 groups (6 animals). Groups included: wild type mice (WT), genetically modified with reduced VAChT (VAChTKD), and those sensitized with ovalbumin (VAChTKDA), exposed to metal powder due to iron pelletizing in mining company (Local1) or 3.21 miles away from a mining company (Local2) in their locations for 2 weeks during summer and winter seasons. It was analyzed for hyperresponsivity, inflammation, remodeling, oxidative stress responses and the cholinergic system. Results During summer, animals without changes in the cholinergic system revealed that Local1 exposure increased the hyperresponsiveness (%Rrs, %Raw), and inflammation (IL-17) relative to vivarium animals, while animals exposed to Local2 also exhibited elevated IL-17. During winter, animals without changes in the cholinergic system revealed that Local2 exposure increased the hyperresponsiveness (%Rrs) relative to vivarium animals. Comparing the exposure local of these animals during summer, animals exposed to Local1 showed elevated %Rrs, Raw, and IL-5 compared to Local 2, while in winter, Local2 exposure led to more IL-17 than Local1. Animals with VAChT attenuation displayed increased %Rrs, NFkappaB, IL-5, and IL-13 but reduced alpha-7 compared to animals without changes in the cholinergic system WT. Animals with VAChT attenuation and asthma showed increased the hyperresponsiveness, all inflammatory markers, remodeling and oxidative stress compared to animals without chronic lung inflammation. Exposure to Local1 exacerbated the hyperresponsiveness, oxidative stressand inflammation in animals with VAChT attenuation associated asthma, while Local2 exposure led to increased inflammation, remodeling and oxidative stress. Conclusions Reduced cholinergic signaling amplifies lung inflammation in a model of chronic allergic lung inflammation. Furthermore, when associated with pollution, it can aggravate specific responses related to inflammation, oxidative stress, and remodeling.